2015
DOI: 10.1159/000430185
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-1β Promotes Epithelial-Derived Alveolar Elastogenesis via αvβ6 Integrin-Dependent TGF-β Activation

Abstract: These data support the hypothesis that IL-1β was initially induced by hyperoxia; αvβ6 subsequently interacted with and activated TGF-β1, acting as an epithelial/mesenchymal signaling molecule that contributed to excessive alveolar elastogenesis, the primary pathological feature of BPD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 50 publications
2
14
0
Order By: Relevance
“…showed that TGF-β1 induces the conversion of primary kidney fibroblasts into myofibroblasts, increases the expression of α-smooth muscle actin (α-SMA), activates the synthesis of fibronectin, and up-regulates the expression of collagen type I (collagen I) in vitro . Similar effects of TGF-β1 were reported in studies on pulmonary fibrosis [7, 8]. …”
Section: Introductionsupporting
confidence: 83%
“…showed that TGF-β1 induces the conversion of primary kidney fibroblasts into myofibroblasts, increases the expression of α-smooth muscle actin (α-SMA), activates the synthesis of fibronectin, and up-regulates the expression of collagen type I (collagen I) in vitro . Similar effects of TGF-β1 were reported in studies on pulmonary fibrosis [7, 8]. …”
Section: Introductionsupporting
confidence: 83%
“…IL-1β and IL-18 are two closely related pro-inflammatory cytokines of interleukin-I family, and play pivotal roles in various immune reactions. Wang et al demonstrated that IL-1β was initially induced in hyperoxia-induced bronchopulmonary dysplasia [37]. In the present study, the hyperoxia-induced activation of NLRP3 inflammasome was inhibited, and the increased levels of IL-1β and IL-18, enhanced activity of caspase-1 in lung tissues were also suppressed in Dex treatment group.…”
Section: Discussionsupporting
confidence: 61%
“…EndMT is a type of EMT (Epithelial-mesenchymal transition) that specifically refers to vascular/cardiac endothelial cells undergoing mesenchymal transition [12, 36-39], which contributes to angiopoiesis and pathological fibrosis mainly in human vascular diseases [40]. EndMT can be induced by multiple factors via several interactive signaling pathways.…”
Section: Discussionmentioning
confidence: 99%